Improving energy efficiency through technology trends, investment behaviour and policy design - Florax, Raymond J. G. M.; Groot, Henri L. F. de.; Mulder, Peter; Edward Elgar Publishing (Cheltenham, U.K. : Edward Elgar, 2011)
This innovative book explores the adoption of energy-saving technologies and their impact on energy efficiency improvements. It contains a mix of theoretical and empirical contributions, and combines and compares economic and physical indicators to monitor and analyse trends in energy efficiency.
pt. 1. Trends in energy efficiency -- pt. 2. Technology and investment behaviour -- pt. 3. Energy policy design.
Includes bibliographical references and index.
Keywords: Energy conservation -- Technological innovations; Energy policy; Electronic books